Igniting Learners’ Behavior And Language Development Through Cartoon Movies: A Phenomenological Study - Paron, Gijet C. (Shanti Journal, 2022)
Children at the current days were more exposed to different cartoon movies. This study aimed to uncover the different experiences and observations of parents in their children who were exposed to cartoon movies. It employed a phenomenological design which structures the consciousness of experiences of the informants. Results revealed that the learners exhibited the abilities to ask excessive questions, articulated words clearly, increased language awareness, and imitated and mimicked conversation. Pedagogical implications are incorporated which strengthen language acquisition among the children.